Ab initio intermolecular potentials and prediction of vapor-liquid equilibria for system N2 and O2 using Gibbs ensemble Monte Carlo simulation - Tất, Phạm Văn (Vietnam Journal of Chemistry, 2012)
The vapor-liquid equilibria of diatomic systems N2 and O2 were predicted by Gibbs ensemble Monte Carlo simulation techniques using the our new developed site-site intermolecular potential [6] and a  Morse-style pair potential [4]. These pair potentials were constructed from ab initio intermolecular energies SAPT (symmetry-adapted perturbation theory), using the level of theory equivalent to fourth-order Müller-Plesset perturbation theory [1]. The critical properties, thermodynamic properties and orthobaric densities based on them are found to be in very good agreement with experimental data.